The Mexican State and the evangelization educational process in northern Sinaloa, 1930-1940 - Santos Cenobio, Rafael (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2015)
This paper deals with the cultural revolution in the post-revolutionary Mexico, which runs from 1930 to 1940 in northern Sinaloa. The first point relates to the different educational policies undertaken by the Ministry of Public Education, in order to incorporate vast masses of peasants and workers to the national State. The role played by primary school teachers in rural communities is also analyzed, specifically as pedagogues, agricultural leaders and union advisors. In this sense, teachers performed as articulators between the Mexican State and peasant communities and other sectors of the population.